PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING DALAM MENINGKATKAN HASIL BELAJAR PPKn KELAS X DI SMA SWASTA BINA KASIH KECAMATAN ARAMO - Seriman Ndruru (Universitas Nias Raya, 2024)
The problem with this sentence is that it reduces students' learning motivation and leads to low learning outcomes. The purpose of this article is to determine the application of the problem learning model to improve PPKn learning. This letter uses the type of